2017
DOI: 10.1007/s00421-017-3658-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passive heat stress and exercise in the heat on arterial stiffness

Abstract: Heat stress via exercise in the heat does not acutely change arterial stiffness. However, passive heating reduces U , indicating that heat stress has an independent effect on PWV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
2
13
1
Order By: Relevance
“…The present findings of local stiffness are in agreement with past whole body and two leg hyperthermia studies which reported no changes in regional (carotid–radial) arterial stiffness (Ganio et al, 2011 ; Moyen et al, 2016 ; Schlader et al, 2019 ). However, studies exploring the recovery following hyperthermia, reported decreases in peripheral and/or leg (femoral–ankle region) arterial stiffness alongside an elevated core temperature (Caldwell et al, 2017 ; Cheng et al, 2021 ; Lee et al, 2018 ; Sugawara & Tomoto, 2021 ; Thomas et al, 2017 ). The latter observations contrast with the unaffected or small changes in arterial stiffness/distensibility, core temperature, and arterial pressure observed in the present and previous single leg heating studies (Chiesa et al, 2015 , 2016 ; Engelland et al, 2020 ; Takahashi et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings of local stiffness are in agreement with past whole body and two leg hyperthermia studies which reported no changes in regional (carotid–radial) arterial stiffness (Ganio et al, 2011 ; Moyen et al, 2016 ; Schlader et al, 2019 ). However, studies exploring the recovery following hyperthermia, reported decreases in peripheral and/or leg (femoral–ankle region) arterial stiffness alongside an elevated core temperature (Caldwell et al, 2017 ; Cheng et al, 2021 ; Lee et al, 2018 ; Sugawara & Tomoto, 2021 ; Thomas et al, 2017 ). The latter observations contrast with the unaffected or small changes in arterial stiffness/distensibility, core temperature, and arterial pressure observed in the present and previous single leg heating studies (Chiesa et al, 2015 , 2016 ; Engelland et al, 2020 ; Takahashi et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The latter observations contrast with the unaffected or small changes in arterial stiffness/distensibility, core temperature, and arterial pressure observed in the present and previous single leg heating studies (Chiesa et al, 2015 , 2016 ; Engelland et al, 2020 ; Takahashi et al, 2011 ). Previous studies have alluded to the possibility that a certain threshold of hyperthermic intensity—such that can initiate profound increases in core temperature and/or alterations in sympathetic activity—may be required to elicit reductions in arterial stiffness and associated increases in distensibility (Caldwell et al, 2017 ; Kaldur et al, 2016 ). Therefore, although further studies are warranted, the present findings indicate that single leg hyperthermia does not alter CFA stiffness and distensibility and thus, conduit artery vascular tone in conditions evoking no or negligible elevations in core temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, passive heating has been shown to reduce PWV. 41 In addition to increased body temperature and its positive effects, sauna bathing may have decreased plasma volume which is further related to changes in haemodynamic parameters such as decreased AS and systemic BP. Therefore, it is possible that heat therapy such as sauna may reduce AS via body dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, passive heat stress is often found to acutely reduce vascular stiffness in younger individuals (Caldwell et al. ). However, the magnitude of these reductions is often dependent on baseline arterial stiffness before passive heat stress.…”
Section: Introductionmentioning
confidence: 99%